A comparison of livestock grazing effects on sagebrush steppe, USA, and Patagonia steppe, Argentina - Adler, Peter B., author; Lauenroth, Bill, advisor; Milchunas, Daniel, committee member; Detling, Jim, committee member (Colorado State University. Libraries, 2003)
Grazing by domestic livestock has dramatic effects on vegetation in some ecosystems but only subtle effects in others. Ecosystem response to grazing is determined by the frequency and degree of plant functional traits related to grazing tolerance and avoidance, which, in turn, are influenced by both precipitation and evolutionary history of grazing. To test the power of evolutionary history to explain variability in the effects of grazing on vegetation, I compared vegetation response to grazing in the sagebrush steppe of North American and the Patagonian steppe of South American. These regions have very similar precipitation regimes, but evidence suggests a shorter evolutionary history of grazing in sagebrush compared to Patagonian steppe. Therefore, I expected the Patagonian steppe to be more grazing resistant than sagebrush steppe.

My comparison of plant traits showed that sagebrush steppe grasses have significantly higher forage quality than Patagonian grasses, based on measurements of tissue nitrogen and fiber content. Sagebrush steppe grasses also tend to be taller than Patagonian grasses. These characteristics may explain why consum ption and utilization by livestock are higher in sagebrush steppe. As a consequence of more intense grazing, decreases in perennial grass production and cover and increases in shrub abundance across distance from water gradients, proxies for historical grazing impacts, were more dramatic in sagebrush than Patagonian steppe. The grazing resistance of Patagonian steppe, therefore, appears to depend on the low forage quality of the dominant grasses.

Evolutionary history of grazing offers one possible explanation for lower forage quality in Patagonian grasses, since it may have evolved as a defense against grazing. However, differences in abiotic factors lead to an alternative explanation: Patagonia’s more extensive arid zone might have favored the evolution of xerophytic traits, and potential nitrogen limitation created by sandy soils could explain the low N content of the dominant grasses. Consistent with this hypothesis, total soil N was much lower in arid Patagonia, where soils are extremely sandy, than in sagebrush sites with similar levels of aboveground production. Understanding the evolution of plant traits will require unraveling the interacting effects of abiotic factors and evolutionary history of grazing.
Keywords: ecology; range management